Households participation in waste management program in Mekong River Delta Vietnam: Parametric and non-parametric approaches - Tien Dung Khong; Xuan Thi Dan Huynh (Journal of Social, Humanity, and Education, 2022)
Purpose: This study aims to estimate households' willingness to pay (WTP) in the Mekong River Delta for the improvement of solid waste (SW) management and identify factors influencing willingness to pay for the improvement program. Then, based on the results, this research proposed some policy implications for better SW management. Research methodology: The research employed both Contingent Valuation Methodology - CVM employed parametric and non-parametric approaches to estimate WTP and Logit model to identify the determinants of WTP. Results: The results from a random survey of 400 observations from 3 main cities in the Mekong River Delta (MRD) indicate that households’ willingness to pay level is from 86,000 Vietnamese Dong (VND) to 110,000 VND/month/household for the non-parametric and parametric approach, respectively (US$1 was equal to 22,890 VND on June 30th, 2021). The results also determine the factors influencing the decision to pay for the program, including bid level, households who have already classified waste, households who intend to support the program, and households’ income. Limitations: In future research, survey areas should be expanded to other developing countries in order to compare and provide a base for proposing better waste management programs in developing countries. Contribution: Future studies should apply both approaches to check the consistency of willingness to pay value elicited. Besides, in order to encourage households to participate in the waste classification program, the authorities need to raise awareness and encourage higher-income households to participate in advance.